2010
DOI: 10.1016/j.icheatmasstransfer.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of natural convection heat transfer coefficients in an attic shaped enclosure

Abstract: The use of convection suppression devices has been widely discussed in the literature as a means of reducing natural convection heat loss from enclosed spaces. In this study the use of a single baffle was examined as a possible low cost means of suppressing heat loss by natural convection in an attic shaped enclosure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Heat transfer by conduction through the floor of the attic would be reduced by insulation, but other heat transfer mechanisms inside the attic would need to be dealt with, such as convection and radiation. [18][19][20][21] The attics…”
Section: Simulation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Heat transfer by conduction through the floor of the attic would be reduced by insulation, but other heat transfer mechanisms inside the attic would need to be dealt with, such as convection and radiation. [18][19][20][21] The attics…”
Section: Simulation Methodologymentioning
confidence: 99%
“…The heat exchange within this space should be governed by convection and radiation. 25 Even in a sealed attic there would always be fluid motion and consequently heat transfer by convection 18 due to temperature difference between surfaces and the air. The average air temperature as well as the interior surfaces of the southern slope and the floor of each attic during winter and summer period are shown in Table 4.…”
Section: Comparative Analysis Of the Reference Atticsmentioning
confidence: 99%
“…With increase in the pitch angle, the number of cells reduced, thereby reducing the heat transfer. Anderson et al [5] determined the heat transfer coefficient for various aspect ratio in an attic shaped enclosure. They suggested a correlation for Nusselt number in terms of the Grashof number as well as the aspect ratio of the attic shaped enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…But no significant changes in the overall heat transfer rate occur for different positions of the baffles. Anderson et al [11] experimentally demonstrated that the use of a single baffle could be examined as a possible low cost means of suppressing heat loss by natural convection in an attic shaped enclosure. Authors found that the heat transfer coefficient changes with increasing baffle length.…”
Section: Introductionmentioning
confidence: 99%